Relationship between Apprenticeship Training with Information and Communication Technologies at Vocational High School in West Java Province - Maulana, A.; Jun, G. J. (INVOTEC, 2018)
The aim of vocational education is to produce employees who are ready to work, a characteristic of vocational education is through the implementation of apprenticeship. In the period 2010-2015 in Indonesia the labor force declined from vocational schools compared to senior high schools. This indicates the need for 21st century skill is called a tool for work, namely the skill to use Information and Communication Technologies (ICT). This article is intended to find out the relationship between apprenticeship and ICT in vocational students who carry out apprenticeship in the province of West Java. From the instrument distributed in 520 samples, it was found that there is a relationship between apprenticeship training and ICT through the value of Zcount = 7.16 Ztable = 2.58, with the coefficient of determination of (ry)2 = (0.315)2 = 0.0992. This shows that apprenticeship contributions affect ICT skill by 9.92% for students who carry out apprenticeship in the West Java province of Indonesia, while 90.08% is influenced by other factors.